Implementation of Doodle Jump Game Based on Accelerometer Sensor and Kalman Filter - Edghar Danuwijaya; Yohanes Armenian Putra; Hilal Hudan Nuha; Ikke Dian Oktaviani (Jurnal Sisfokom)
The doodle jump game is a video game with a jumping game model assisted by accelerometer sensor technology. Placing the accelerometer sensor in the doodle jump game is a very appropriate solution to determine the accuracy of the values on the sensor. The accelerometer sensor can be measured in real time, however applying a small force to the sensor can result in interference with measurement accuracy. Therefore, creating the measurement results you need using filters can help reduce noise. The method used to use this filter is the Kalman Filter algorithm. The use of the Kalman Filter method can provide a stable level of accuracy in the movements of the main characters in the game and the accelerometer sensor so that it can become a precise algorithm. This research has successfully influenced the accuracy of the accelerometer sensor, as an example of using the performance of the accelerometer sensor and the application of Kalman filter has an accuracy difference of 20.70% for the right tilt detection results and 33.25% for the left tilt detection results. This indicates that the application of the Kalman filter to the Doodle Jump game can have a significant effect.